2019
DOI: 10.1177/1538574419867531
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fluid Dynamics Variations Between Chimney and Fenestrated Endografts for Pararenal Aneurysms Repair: A Patient Specific Computational Study as Motivation for Clinical Decision-Making

Abstract: Background-Aim: Limited data exist concerning the fluid dynamic changes induced by endovascular aortic repair with fenestrated and chimney graft modalities in pararenal aneurysms. We aimed to investigate and compare the wall shear stress (WSS) and flow dynamics for the branch vessels before and after endovascular aortic repair with fenestrated and chimney techniques. Methods: Modeling was done for patient specific pararenal aortic aneurysms employing fenestrated and chimney grafts (Materialise Mimics 10.0) bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Lamooki et al noticed that computer modeling of stent expansion is critical for preventing unrealistic bulging effects and thus should be considered in virtual flow diverter deployment algorithms [ 47 ]. Patient specific AAA blood hemodynamic simulation is a promising tool that may provide important information for understanding hemodynamic factors involved in AAA repair and potentially provide data for clinical decision making [ 48 ]. In our study, as well as in Harrison et al, no comparison between the effects of the different mechanical properties of the patch and of the native artery in terms of disturbed flow [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lamooki et al noticed that computer modeling of stent expansion is critical for preventing unrealistic bulging effects and thus should be considered in virtual flow diverter deployment algorithms [ 47 ]. Patient specific AAA blood hemodynamic simulation is a promising tool that may provide important information for understanding hemodynamic factors involved in AAA repair and potentially provide data for clinical decision making [ 48 ]. In our study, as well as in Harrison et al, no comparison between the effects of the different mechanical properties of the patch and of the native artery in terms of disturbed flow [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The maximum diameters of the aortic aneurysms were measured from the images, with 55.41 mm for case I and 65.89 mm for case II. To ensure smooth and accurate representations, we applied a previously published smoothing approach 17 . Firstly, a mask was created on the CT scans by selecting an appropriate brightness threshold and properly cropping the region of interest to isolate the pure blood flow aortic and vascular lumens.…”
Section: Methodsmentioning
confidence: 99%
“…However, this study did not investigate the effect of supra‐arch vessels reconstruction. Konstantinos et al 15 performed CFD simulations on two patients with abdominal aortic aneurysms treated with chimney technique and fenestration technique, respectively, and found that compared with the fenestration model, the perfusion of the kidney with the chimney stent was significantly reduced. Asaph Nardi et al 16 studied the preoperative aorta of patients with aortic arch aneurysm, the aorta after aortic arch replacement, chimney technique and hybrid technology, and performed CFD simulations.…”
Section: Introductionmentioning
confidence: 99%